The impact of abusive supervision on the functions of supervision in social work - Vîșcu, Loredana; Rad, Dana (Technium Social Sciences Journal, 2024)
Supervision in social work is an organizational, individual need towards the well-being of the supervisee and the beneficiary. In general, professional supervision has gained its undeniable role, in particular, supervision in social work bears the imprint of clinical supervision and organizational supervision. The professionalization of the profession of psychotherapist has also attracted social workers interested in acquiring psychotherapeutic skills, and the social work profession is moving towards liberalization. As in psychotherapy, psychological counseling there are models of supervision in social work. The aim of the paper is to present the functions of supervision in social work from an integrative perspective (individual, organization) and the consequences of abusive supervision in the exercise of supervisory functions in Philip Rich’s model. The supervisor in social work needs a holistic view: supervisee (needs of the supervisee)-organization (organizational needs)-social, social consequences of supervision (needs of the beneficiaries). A supervision with the focus on the supervisee, organization, social will not generate favorable consequences, on the contrary, it creates the premises for abusive supervision and hence, the decrease of the supervisor’s creativity, task conflicts, bournaout, social undermining.